(untitled) (Research, Society and Development, 2019)
Occupational Health is the promotion of labor conditions to ensure the highest degree of quality of life at work, protecting the health of workers, promoting the physical well-being, mental and social health, preventing and controlling diseases and injuries by reducing threatening conditions. The most frequent problems of professionals dealing with occupational health are fractures, cuts and sprains from accidents at work, repetitive motion disorders, problems with vision and hearing and the diseases caused by exposure to substances unhygienic or radioactive. Also can encounter stress caused by work or by relations. Occupational health is an important issue for governments, which must ensure the well-being of workers and compliance with the scope of work. We aimed to observe how occur periodic inspections to determine the conditions under which they are developed various types of work activities. Thus, it is important to analyze how the management acts of workplace accidents within companies. Through the review it was observed that besides the recognition of technical failures of security is lacking in the safety management system that need to be considered in the cast of prevention recommendations to be presented to the company in the outcome of the intervention surveillance, and thus record, process, analyze and define improvement plans to reduce accidents and incidents at work.